Resistência anti-helmíntica de nematódeos gastrintestinais de ovinos da região Noroeste do Estado de São Paulo - Kaneto, Carlos Noriyuki [UNESP]; Cardia, Daniel Fontana Ferreira; Gomes, Jancarlo Ferreira; De Matos, Lucas Vinicius Shigaki [UNESP]; Pierucci, Julia Cestari [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2016)
The occurrence of anthelmintic resistance of gastrointestinal nematodes was investigated on 11 sheep farms of the Northwest region of the State of São Paulo. The tested anthelmintics belong to the groups of the benzimidazoles, imidothiazoles, salicylanilides and macrocyclic lactones. The anthelmintic resistance was considered patent when the egg count reduction in feces was less than 90.0%, evaluated between seven and 14 days after the use of the drugs, using the fecal egg count reduction test according to World Association for the Advancement of Veterinary Parasitology (W.A.A.V.P.). The identification of the genera of gastrointestinal nematodes resistant to anthelmintics present in the properties studied was verified by larvae cultures. From 10 herds evaluated for the efficacy of moxidectin, five (50.0%) were resistant to it. Six (54.5%) of 11 herds evidenced resistance to the levamisole. Resistance to the closantel was observed in 10 (90.9%) of 11 farms examined. Resistance to the ivermectin and albendazole was detected in all farms and Haemonchus spp. was the most predominant nematode genus. Therefore, we report the existence of multiple anthelmintic resistance in gastrointestinal nematodes of sheep in the Northwest region of the State of São Paulo.
Keywords: Helminth; Ovine; Parasite; Treatment